The Role of Cholesterol Homeostasis in Diabetic Kidney Disease - Chen, Xinyun; Yin, Qinghua; Ma, Liang; Fu, Ping (Current Medicinal Chemistry, 2021)
Considerable evidence has proved that disturbed cholesterol metabolism played a crucial role in diabetic kidney disease. Besides, massive cholesterol depositions were found in intrinsic renal cells of diabetic kidney disease patients and animal models, causing cytotoxicity and affecting renal function. Statins could alleviate cholesterol depositions, podocyte injury, and microalbuminuria of diabetic kidney disease. In this review, we summarized the process of disturbed cholesterol metabolism and discussed how it induced kidney dysfunction in diabetic kidney disease.
Keywords: ABCA1